Special needs children in performing given tasks - Aclnis Sombuling; Murnizam Hj. Halik; Balan Rathakrisnan; Joki Perdani Sawai; Sharon Kwan Sam Mee; Esther Tsen Pui Sheong; Chua Yee Chii (Universiti Malaysia Sabah, 2012)
The core of this research was to investigate the different abilities of planning and working memory among autisms and slow learners based on gender, age and parents' occupation. A total of 60 autisms and slow \earners from aged 9-14 years old were recruited. The Tower of Hanoi (ToH) and Children Memory Scale (G1S: Dot Location II) were used to assess the abilities of planning and working memory respectively. The result showed that there were no signifICant differences between autisms and slow \earners in both abilities of planning and working memory based on.gender and parents' occupation. However, the finding showed significant influence of age in both planning and working memory among autisms and slow learners. Therefore, it is necessary to evaluate the empirical evidence in concerning the differences of cognitive process among the autisms and slow learners and also discovery other factors that may influence the special needs children's performance.